Nilai Moral Terkait Hubungan Manusia dalam Novel Khadijah: Ketika Rahasia م (Mim) Tersingkap - Umi Lestari; Lulus Irawati; Dwi Rohman Soleh (Universitas PGRI Madiun, 2022)
Umi Lestari, 2022. Moral values of novel Novel Khadijah : Rahasia Mim Tersingkap by Sibel Eraslan. This recearch aims to get moral values from novel Khadijah : Rahasia Mim Tersingkap written by Sibel Eraslan.The method used in this research is qualitative descriptive. The data resours used is Novel Khadijah : Rahasia Mim Tersingkap by Sibel Eraslan. The insrument of getting data si the researher and the technique is document from Novel Khadijah : Rahasia Mim Tersingkap by Sibel Eraslan. The techique of data analysis is examine the whole documents.The result of this research is to find out the moral values fron Novel Khadijah : Rahasia Mim Tersingkap by Sibel Eraslan relates to the relations between human and other people and nature. The moral values found are generous, or helpful, affection, keep friendship, empathy, respect to parents, work together, respect to guesst, politeness, empathy , conference, and relation to nature.